2019
DOI: 10.1186/s12911-018-0717-4
|View full text |Cite
|
Sign up to set email alerts
|

A classification framework for exploiting sparse multi-variate temporal features with application to adverse drug event detection in medical records

Abstract: BackgroundAdverse drug events (ADEs) as well as other preventable adverse events in the hospital setting incur a yearly monetary cost of approximately $3.5 billion, in the United States alone. Therefore, it is of paramount importance to reduce the impact and prevalence of ADEs within the healthcare sector, not only since it will result in reducing human suffering, but also as a means to substantially reduce economical strains on the healthcare system. One approach to mitigate this problem is to employ predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…A recent study described the development of multiple risk prediction models. 36 The authors utilised a de-identified dataset from a Swedish hospital. A series of ICD-10 codes related to the diagnosis of medication harm were used as the outcomes for models (e.g.…”
Section: And Automated Harm Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study described the development of multiple risk prediction models. 36 The authors utilised a de-identified dataset from a Swedish hospital. A series of ICD-10 codes related to the diagnosis of medication harm were used as the outcomes for models (e.g.…”
Section: And Automated Harm Detectionmentioning
confidence: 99%
“…causality assessment to ensure codes were correctly allocated). 36 An Australian study also reported using ML and ICD codes to detect medication harm in a tertiary hospital. The automated algorithm demonstrated promising performance with an AUC of 0.803.…”
Section: And Automated Harm Detectionmentioning
confidence: 99%
“…Diagnostic errors are common and it is estimated that everyone will experience at least one diagnostic error in their lifetime 1 . Although there is general agreement on co- or multi-morbidities complicating the diagnostic procedure resulting in higher risk for erroneous diagnoses, definitions for erroneous diagnoses lack consistency and several terms are used to refer to flawed diagnoses 2 5 . The terms misdiagnosis and overdiagnosis are often used interchangeably and they can be difficult to distinguish 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, no methods to identify overdiagnosis at the single patient level have been developed. Hence, there is a need to systematically identify patients at risk of mis- and overdiagnosis, leading to unnecessary harm from treatments and potentially missed underlying diseases 5 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Writers may explicitly state an apparent association between treatment and adverse outcome (“attributed”) or state the simple treatment and outcome without an association (“unattributed”). More critically, attributed and unattributed potential AEs (PAEs) may not necessarily be captured in structured data (e.g., diagnosis and procedure codes) [14, 23, 39].…”
Section: Introductionmentioning
confidence: 99%